Natural Stone Mining Activities on the Foothills of Mount Ungaran in Ethnoecological Perspective (Faculty of Social Science, Universitas Negeri Semarang, 2021)
Ndhepo is a stone mining activity in illegal sites carried out by the people of Medono Village. This activity is one of the changes in environment utilization. This study proposes to determine the perception of the people of Medono Village with the existence of stone mining activities around their living environment, to find out the meaning of the Medono Village community regarding their living environment, and to obtain the reasons for the community to carry out stone mining activities. The research method of this study was qualitative. Data analysis used an ethnoecological perspective. The results indicate that the natural environment in Medono Village is a fertile area and saves other natural resources, namely natural mineral resources for excavation C in the form of andesite rocks. Before the ndhepo activity, the community used their land for agricultural purposes. However, after realizing that ndhepo could provide a higher income than cultivating agricultural land, some people then turned to mine workers. The Medono Village community interprets the environment as a place to meet the needs of life. However, there are other meanings by most people, especially those related to stone mining activities because they have an impact on the surrounding natural environment. Some citizens actually do not approve of the existence of those mining activities.